Freshwater Ornamental Fish Commonly Cultured in Florida - Jeffrey E. Hill; Roy Yanong (EDIS, 2013)
Fish can be grouped in a number of different ways. One major division in the industry which has practical significance is that between egg-laying species and live-bearing species. The culture practices for each division are different, requiring specialized knowledge and equipment to succeed.